Can Memories of Traumatic Experiences or Addiction Be Erased or Modified? A Critical Review of Research on the Disruption of Memory Reconsolidation and Its Applications. (March 2017) - Treanor, Michael; Brown, Lily A.; Rissman, Jesse; Craske, Michelle G.
Recent research suggests that the mere act of retrieving a memory can temporarily make that memory vulnerable to disruption. This process of "reconsolidation" will typically restabilize the neural representation of the memory and foster its long-term storage. However, the process of reconsolidating the memory takes time to complete, and during this limited time window, the original memory may be modified either by the presentation of new information or with pharmacological agents. Such findings have prompted rising interest in using disruption during reconsolidation as a clinical intervention for anxiety, posttraumatic stress, and substance use disorders. However, "boundary conditions" on memory reconsolidation may pose significant obstacles to clinical translation. The aim of this article is to critically examine the nature of these boundary conditions, their neurobiological substrates, and the potential effect they may have on disruption of reconsolidation as a clinical intervention. These boundary conditions also highlight potential constraints on the reconsolidation phenomenon and suggest a limited role for memory updating consistent with evolutionary accounts of associative learning for threat and reward. We conclude with suggestions for future research needed to elucidate the precise conditions under which reconsolidation disruption may be clinically useful.